Estudo do efeito antipsicótico do extrato etanólico padronizado da Erythrina velutina Willd em modelo de esquizofrenia induzido por cetamina em camundongos. - Dias, Katia Cilene Ferreira (2018)
Schizophrenia is a chronic mental illness characterized by positive, negative and cognitive symptoms. Plants have been studied to treat Central Nervous System disorders such as an Erythrina velutina Willd. Previous studies have demonstrated neuroprotective and antioxidant activities. Here, we aimed to study the effects of the standardized extract of Erythrina velutina leaves on its behavioral, oxidative and protein expression of inflammatory mediators in the ketamine model for schizophrenia in mice. Male mice (25 g) received ketamine (KET) (25 mg/kg, i.p.) or repeated saline administration for 7 days. From day 8 to day 14 animals received Erythrina (ERYT) (100, 200 or 400 mg/kg, o.p.) or olanzapine (1 mg/kg, o.p.) 1 hour after CET administration. On the 14th day, 30 minutes after a new KET administration, we performed the open field test and the pre-pulse inhibition (PPI) tests. Afterward, all animals were euthanized and the prefrontal cortex (PFC), hippocampus (HC) and striatum (ST) were dissected to measure oxidative and nitrergic stress markers. After choosing the dose with the best behavioral effect, Western blotting was performed on the PFC for the evaluation of protein mediators of inflammation such as NFkB, Iba-1, Akt, and phospho-Akt. Our results showed that KET increased the spontaneous locomotor activity and the number of grooming of the animals when compared to the control group. KET decreased the PPI in the three pulses studied, this effect was reversed by the combination of ERYT with olanzapine. KET decreased the GSH concentration in the PFC when compared to the control group, and it was reversed by the association with ERYT in the lower doses. KET reduced the concentration of GSH in ST, this effect was reverted by ERYT at the lower dose. KET increased MDA concentration in PFC and HC compared to control groups, this effect was reversed by association with ERYT at all doses. ERYT and Olanzapine reduced the concentration of MDA in ST when compared to the KET group. The nitrite levels were decreased only in the PFC when compared to the control group, and it was reversed only by the combination with olanzapine. Decreased nitrate levels were observed in the Erythrina combination groups (ERYT 200 or 400 + KET) when compared to the control group. No alteration in the levels of Iba-1, NFkB and Akt protein expression was observed at the dose of 400mg/kg, although phosphor-Akt showed a tendency to increase. Our findings demonstrate that the standardized extract of Erythrina velutina can reduce positive and negative-like behaviors associated with schizophrenia and the oxidative stress induced by repeated doses of KET. Our study suggests a new perspective on the treatment of schizophrenia.